Evaluation of Serum Adropin, Irisin, and Preptin Levels in Individuals with Benign Prostatic Hyperplasia and Prostate Cancer - Susam, Solmaz; Ilhan, Nevin; Yıldız, Furkan; Berk, Buket (My University, 2025)
Benign prostatic hyperplasia (BPH) and prostate cancer (PCa) are common urological conditions among aging men, characterized by benign enlargement and malignant progression of the prostate gland, respectively. This study was designed to answer the question of whether adropin, irisin, and preptin serum levels have an impact on the development of prostate disease in a total of 90 participants, including BPH (n=30), localized PCa (n=30), and healthy controls (n=30). The serum concentrations of these peptides were determined using enzyme-linked immunosorbent assay (ELISA). According to the findings, adropin and irisin levels were significantly lower in the BPH and PCa groups compared to the control group (p<0.001). Conversely, preptin levels were significantly higher in both the BPH and PCa groups compared to the control group (p<0.001), with preptin levels in the PCa group being higher than those in the BPH group (p<0.001). In conclusion, these findings highlight the complex interactions of these peptides in prostate pathophysiology, suggesting that adropin and irisin may be linked to metabolic dysregulation, while preptin is associated with cellular growth processes related to prostate malignancies. Furthermore, this study emphasizes the need for further studies to elucidate the specific roles and therapeutic potential of adropin, irisin and preptin in the management of prostate health and disease.
Keywords: BPH; Adropin; Irisin; Preptin; Prostate health